Determinants of Agroedutourism Development: A Case Study of Orange Picking Tourism at Politeknik Negeri Jember - Nadhirah, Aulia; Napitupulu, Tia Sofiani; Sumarlina, Sumarlina; Marseva, Amalia Dwi; Kinanti, Lintang Anis Bena; Pradini, Anggieta Yuni (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
Agroedutourism has emerged as a sustainable tourism model that integrates recreational activities with agricultural education, offering both experiential learning and economic value. This study analyzes the determinants of agroedutourism development at the orange picking site of the Teaching Factory (TeFa) Kebun Inovasi Politeknik Negeri Jember (Polije). The objectives are to identify the potential attractions of orange-based agroedutourism and to evaluate the influence of attraction, accessibility, amenities, and visitor perceptions on destination development. Data were obtained through field observations, interviews with management and academic experts, and surveys of 125 visitors. A descriptive approach was used to assess the site’s potential, while multiple linear regression was applied to examine the effect of the four determinant variables. The results indicate that TeFa Kebun Inovasi has strong agroedutourism potential, supported by commodity diversity, educational value, scenic landscapes, and opportunities for local product development. Regression analysis shows that attraction, accessibility, amenities, and perception collectively have a significant effect on agroedutourism development (F = 213.927; p < 0.05). However, only visitor perception exhibits a significant individual influence (β = 0.873; p < 0.001), suggesting that visitor experience acts as the primary driver of development. Physical factors such as attraction, accessibility, and amenities contribute positively but do not show significant independent effects. These findings highlight the importance of enhancing experiential quality, educational engagement, and service interaction to strengthen visitor perception. Improving facilities, infrastructure, and thematic attractions remains essential to support a comprehensive and competitive agroedutourism model within a vocational education environment.